2012
DOI: 10.6002/ect.2011.0086
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Conversion to Sirolimus Monotherapy After Liver Transplant

Abstract: Objectives: This study sought to assess the longterm efficacy and safety of conversion from a calcineurin inhibitor-based immunosuppressive regimen to sirolimus monotherapy in liver transplant recipients with renal dysfunction. Materials and Methods: Twenty-five liver transplant recipients with calcineurin inhibitor-based immunosuppression were included in this singlecenter, prospective study. Indications were renal dysfunction, avoidance of tumor recurrence, combination renal dysfunction and avoidance of tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…From our literature search, proteinuria was observed in six liver transplant studies of variable quality involving sirolimus use (Table 3(d)) [67, 72, 73, 75, 77, 86]. In one of these, a small, prospective, randomized study, the rate of proteinuria during the 1-year followup was similar to that observed in controls receiving mycophenolate mofetil (MMF) [73].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From our literature search, proteinuria was observed in six liver transplant studies of variable quality involving sirolimus use (Table 3(d)) [67, 72, 73, 75, 77, 86]. In one of these, a small, prospective, randomized study, the rate of proteinuria during the 1-year followup was similar to that observed in controls receiving mycophenolate mofetil (MMF) [73].…”
Section: Resultsmentioning
confidence: 99%
“…Three prospective and four retrospective studies (a mixture of low- and medium quality) demonstrated improvements in renal function in recipients converting to sirolimus [77, 78, 81, 8386]. Two of these studies (one prospective, one retrospective) demonstrated long periods of improved GFR after conversion in sirolimus conversion groups at 27.5 months [81] and up to 60 months after conversion [77]. Two small prospective studies (one low quality, single-arm and one medium quality, randomized) showed only numerical improvements at 6 [82] and 12 [76] months after conversion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The diverse actions of rapamycin on the immune response justify its candidacy as a treatment for autoimmune hepatitis, and limited experiences after liver transplantation have supported its further study in this disease [210][211][212][213][214]. The use of rapamycin has not been reported in patients with autoimmune hepatitis outside of liver transplantation, and this experience has been meager but promising.…”
Section: Rapamycinmentioning
confidence: 89%